PERTIMBANGAN HAKIM MAHKAMAH AGUNG MENGABULKAN KASASI PENUNTUT UMUM DALAM PERKARA PEMBUNUHAN BERENCANA - Safa Rahaynia Sekar Wigati (Sebelas Maret University, 2023)
This study aims to determine the suitability of the Supreme Court's consideration that granted the Cassation of the Public Prosecutor in the Murder Case based on the Supreme Court Decision Number: 1282 K/1282/2020 with the provisions of the Criminal Procedure Code. This research is a prescriptive normative legal research with a case approach (case approach). Legal material collection techniques using literature studies by analyzing primary legal materials and secondary legal materials. The legal material analysis technique used by the deductive syllogism method. The results showed that the consideration of the Supreme Court who granted the Public Prosecutor's Cassation Request so as to cancel the Judex Factie's decision and prosecute the case by stating the defendant was proven to have committed a planned murder in accordance with the provisions of Article 255 paragraph (1) of the Criminal Procedure Code in conjunction with Article 340 of the Criminal Code. The Supreme Court stated that the Judex Factie was wrong in applying the proof law by not paying attention to the legal facts revealed at the trial, where the defendant had been proven to have committed a planned murder because of the fulfillment of the planned element of the plan.Keywords: Cassation; Consideration; Premeditated Murder